12 Prevalence of transthyretin amyloid cardiomyopathy (aTTR-CM) in undifferentiated HFpEF. (6th October 2022) - Healy, L; Giblin, G; O'Sullivan, D; Kavanagh, E; Howley, E; Tracey, C; O'Neill, J; Joyce, E; O'Connell, M; McDaid, A; Clarke, A; Gray, A; et al.
Abstract : Introduction: Transthyretin amyloid cardiomyopathy (aTTR-CM) is an increasingly recognised cause of heart failure with preserved ejection fraction (HFpEF) which may be diagnosed non-invasively with SPECT/CT 99m-3, 3-diphosphono-1, 2-propanodicarboxylic acid (DPD) scintigraphy. The diagnosis of aTTR-CM has assumed greater relevance with the growing availability of targeted treatments. However, there are relatively few studies on the prevalence of aTTR-CM in undifferentiated HFpEF. Aim To determine the prevalence of patients with aTTR-CM in an undifferentiated HFpEF cohort by DPD scintigraphy. Methods: Tc-DPD scintigraphy scan was prospectively performed in patients aged > 60 years attending the Mater Misericordiae University Hospital (MMUH) with a diagnosis of HFpEF (EF>50%) who were New York heart association (NYHA) class II-IV. All patients had an echocardiogram performed at recruitment or within the previous 6 months. Patients with a history of AL amyloid, known cardiac amyloidosis, a history of monoclonal gammopathy of unknown significance (MGUS), significant valvular pathology, recent acute coronary syndrome or uncontrolled arrhythmia were excluded. Results: 81 patients were enrolled, 44 patients (54%) female, 37 patients (43%) male. Mean age 78, mean EF 54%, mean BNP 864 pg/ml, 53 (57%) hypertensive, 53% had atrial fibrillation, 49.5% NYHA II, 49.5% NYHA III, 1% NYHA IV. Heart failure hospitalisation within 1 year occurred in 48 patients (59%). The DPD findings were as follows: Perugini 0: 67 (82.7%), Perugini 1: 7 (8.6%), Perugini 2: 4 (4.9%), Perugini 3: 3 (3.7%). Perugini 2 and 3 patients differed significantly from the remaining cohort by age, gender, QRS width and septal thickness (table 1). Posterior wall thickness, LVDD and left atrial volumes did not differ between cohorts. All Perugini 2 and 3 patients underwent genetic testing and were confirmed as wild-type (WT). Conclusion: This study identified a prevalence of WT aTTR-CM of 8.6% of an undifferentiated HFpEF cohort. There was a striking association with age and gender with 17% of males in this group found to have WT aTTR-CM.